Metagenomic assembly and draft genome sequence of an Uncharacterized prevotella sp. from Nelore rumen - Kishi, Luciano T. [UNESP]; Jesus, Raphael B. de [UNESP]; Pavani, Claudio D. [UNESP]; Lemos, Eliana G M [UNESP]; Souza, Jackson A. M. de [UNESP] (Genome Announcements, 2015)
Prevotella is one of the most abundant genera in bovine rumen, although no genome has yet been assembled by a metagenomics approach applied to Brazilian Nelore. We report the draft genome sequence of Prevotella sp., comprising 2,971,040 bp, obtained using the Illumina sequencing platform. This genome includes 127 contigs and presents a low 48% GC.